EFEKTIFITAS EKSTRAK KULIT DUKU (Lansium domesticum corr) TERHADAP MORTALITAS PEDIKULUS HUMANUS CAPITIS SEBAGAI PENYEBAB PEDIKULOSIS PADA ANAK - Darmadi Darmadi; Dimas Pradhasumitra; Surya Eko Setiawan (JURNAL FARMASI DAN MAKANAN, 2018)
Head lice (Pediculus humanus capitis) is an insect that carries a disease that makes the loss of confidence. Efforts of control and pembutuasan head lice is the use of natural insecticides, one of the plants that have the potential as a natural insecticide is duku skin extract (Lansium domesticum Corr.). The purpose of this study was to determine mortality of head lice (Pediculus humanus capitis) and to know the compounds contained in duku skin extract. The research used laboratory experimental method with design research design post only control group. Based on the result of the research, the most effective rate of death of head louse (Pediculus humanus capitis) is 15% concentration with 4 head of head louse (80%), while at concentration 10% is 2 tail (40%) and at concentration 5% there is a dead head louse 0 (0%). The results of this study can be concluded that duku leaf extract (Lansium domesticum Corr.) Serves as a natural insecticide due to the presence of secondary metabolite compounds that are active in killing head lice (Pediculus humanus capitis).